2021
DOI: 10.1136/jim-2021-001778
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Aortic Stiffness after Substantial Weight Loss by Laparoscopic Sleeve Gastrectomy in Patients with Obesity: A 1-Year Follow-Up Study

Abstract: Arterial stiffness has been identified as a powerful and independent risk factor for cardiovascular disease. Obesity is associated with an increased risk of aortic stiffness (AS) and adverse cardiovascular events. Herein, we aimed to evaluate the effects of weight loss after laparoscopic sleeve gastrectomy (LSG) on AS in individuals with morbid obesity by using the transthoracic echocardiography (TTE).A total of 53 patients with obesity (17 males, 36 females) who underwent LSG and did not have any known heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Ikonomidis et al could show an improved aortic function in 60 individuals after bariatric surgery ( Ikonomidis et al, 2007 ). Similarly, Gul et al observed an improvement of aortic stiffness 1 year after laparoscopic sleeve gastrectomy in 53 obese individuals ( Gul et al, 2021 ). Also, Brinkley et al could demonstrate an improved aortic stiffness in elderly obese after moderate and intensive caloric restriction combined with aerobic exercise training, but not with aerobic exercise training alone ( Brinkley et al, 2021 ).…”
Section: Discussionmentioning
confidence: 88%
“…Ikonomidis et al could show an improved aortic function in 60 individuals after bariatric surgery ( Ikonomidis et al, 2007 ). Similarly, Gul et al observed an improvement of aortic stiffness 1 year after laparoscopic sleeve gastrectomy in 53 obese individuals ( Gul et al, 2021 ). Also, Brinkley et al could demonstrate an improved aortic stiffness in elderly obese after moderate and intensive caloric restriction combined with aerobic exercise training, but not with aerobic exercise training alone ( Brinkley et al, 2021 ).…”
Section: Discussionmentioning
confidence: 88%